Development of a CERGAM book to enhance conceptual understanding of family member roles - Rahayu Rahayu; Eka Yusnaldi (Inovasi Kurikulum, 2025)
Students experience obstacles to understanding the concept of the role of family members due to the limitations of adequate learning facilities that are interesting, and in harmony with their level of development. This research is focused on the development of CERGAM book media to help improve the understanding of MI grade 2 students on the concept of the role of family members, by ensuring that the media meets the criteria of feasibility, practicality, and effectiveness. This study adopts a development approach using the research and development (RnD) method with the ADDIE model involving students and 2nd-grade teachers at MIN 7 Medan City. Data were collected using interviews, observation, expert validation techniques, response questionnaires, learning outcome tests, and documentation. The results of the study show that the material and language indicate that the CERGAM book media produced is in the category of being very valid. The teachers and students gave very positive results and showed that the CERGAM media design was efficient and had the potential to support the teaching and learning process. In addition, the results of the learning evaluation are included in the category of very effective, showing the development of students' understanding of concepts in real terms after they use the CERGAM book media. Overall, this media was stated to meet the criteria of feasibility, practicality, and effectiveness to support students' understanding of the concept of the role of family members among MI grade 2 students.   Abstrak Peserta didik mengalami hambatan untuk memahami konsep peran anggota keluarga akibat keterbatasan sarana belajar yang memadai, menarik, dan selaras dengan tingkat perkembangan mereka. Penelitian ini difokuskan pada pengembangan media buku CERGAM guna membantu meningkatkan pemahaman peserta didik kelas 2 MI terhadap konsep peran anggota keluarga, dengan memastikan bahwa media tersebut memenuhi kriteria kelayakan, kepraktisan, dan keefektifan. Penelitian ini mengadopsi pendekatan pengembangan dengan menggunakan metode riset dan pengembangan (RnD) dengan model ADDIE yang melibatkan peserta didik dan Guru kelas 2 di MIN 7 Kota Medan. Data dikumpulkan menggunakan teknik wawancara, wawancara, observasi, validasi ahli, angket respons, tes hasil belajar, dan dokumentasi. Hasil penelitian menunjukkan bahwa materi serta bahasa mengindikasikan bahwa media buku CERGAM yang dihasilkan berada dalam kategori sangat valid. Para guru dan peserta didik memberikan hasil sangat positif serta menunjukkan bahwa media CERGAM yang dirancang sangat praktis dan berpotensi menunjang proses belajar mengajar. Disamping itu, hasil dari evaluasi pembelajaran termasuk ke dalam kategori sangat efektif, menunjukkan adanya perkembangan pemahaman peserta didik terhadap konsep secara nyata setelah mereka memanfaatkan media buku CERGAM. Secara keseluruhan, media ini dinyatakan memenuhi kriteria kelayakan, kepraktisan, dan keefektifan untuk mendukung pemahaman peserta didik terhadap konsep peran anggota keluarga di kalangan peserta didik kelas 2 MI. Kata Kunci: buku CERGAM; pemahaman konsep; peran anggota keluarga